Faculty productivity in Zambian higher education in the face of internationalization: Unpacking research, publication and citation at the University of Zambia - Gift Masaiti; Kennedy Mwila; Cecilia Kulyambanino; Tommie Njobvu (University of Johannesburg, 2021)
This paper is based on a study that aimed at examining and interrogating the extent of faculty productivity in Zambia in terms of research, publication and citation with specific reference to the University of Zambia (UNZA). The paper invokes the Network Theory of Internationalisation of Higher Education founded by Johanson & Mattsson (1988).The research design used in this article is a convergent parallel mixed-methods design. The sample size total was 254, of which 244 were academic staff and 10 were key informants from management. Qualitative data was analysed according to emerging themes, while quantitative data was analysed using descriptive and inferential statistics. The findings of this paper seem to suggest that faculties at UNZA were highly involved in research (applied and basic) at 75%, but with poor incidences of transforming research into publication and innovation. Only 38% of respondents published articles annually (increasing to 62% within two years) in local and international journals. While respondents who had published books in the last two years was as low as 19.5%. UNZA productivity output in terms of citation was relatively poor, below the expected standard of h-index and citation index of a flagship university which has a track record of more than 40 years of operation as a fully-fledged comprehensive university. Results primarily showed that the UNZA had an average h-index of 4.50 and a citation index of 156.87 which are significantly lower than the world averages of 17.50 and 971, respectively. The paper finally argues that, UNZA like most of the flagship and comprehensive universities in Africa, are quickly transforming from a teaching university into a research university based on the influence of the global North whose research agenda is central - at the expense of teaching. In order to improve on research productivity, this paper recommends that UNZA deliberately identify relevant industries, and global and regional partners to genuinely collaborate with as a way of leveraging resources and expertise. There is also a growing desire by universities in the global South to work closely together as way of improving their own productivity capacity in terms of research, publication, citation and redefine the concept of internationalization to fit the global South.